K−12 teachers' stress and burnout during the COVID-19 pandemic: A systematic review - Westphal, Andrea; Kalinowski, Eva; Hoferichter, Clara Josepha; Vock, Miriam (Frontiers in Psychology, 2022)
We present the first systematic literature review on stress and burnout in K–12 teachers during the COVID-19 pandemic. Based on a systematic literature search, we identified 17 studies that included 9,874 K–12 teachers from around the world. These studies showed some indication that burnout did increase during the COVID-19 pandemic. There were, however, almost no differences in the levels of stress and burnout experienced by K–12 teachers compared to individuals employed in other occupational fields. School principals’ leadership styles emerged as an organizational characteristic that is highly relevant for K–12 teachers’ levels of stress and burnout. Individual teacher characteristics associated with burnout were K–12 teachers’ personality, self-efficacy in online teaching, and perceived vulnerability to COVID-19. In order to reduce stress, there was an indication that stress-management training in combination with training in technology use for teaching may be superior to stress-management training alone. Future research needs to adopt more longitudinal designs and examine the interplay between individual and organizational characteristics in the development of teacher stress and burnout during the COVID-19 pandemic and beyond.